Do Islamic Business Ethics Have An Effect on Indonesian Citizens' Interest in Saving At The Faisal Islamic Bank of Egypt? A Case in Cairo, Egypt. - Fakhrurozi, Fakhrurozi; Najmudin, Najmudin; Maelani, Puspita (MUAMALATUNA, 2022)
This study aims to determine the effect of Islamic business ethics on the interest of Indonesian citizens in Egypt to save at the Faisal Islamic Bank of Egypt. The population in this study were Indonesian students in Egypt who received scholarships at Baitu Az-Zakah al-Quwaity. Respondents of this study amounted to 64 students. The research method used is a quantitative-descriptive method with data collection methods in the form of questionnaires. Data were analyzed using instrument tests in the form of validity and reliability tests, classical assumption tests in the form of normality tests and heteroscedasticity tests, and hypothesis tests in the form of simple linear regression tests and correlation coefficient tests. The results of this study indicate that Islamic business ethics has a significant positive effect on the interest of Indonesian citizens in Egypt to save at the Faisal Islamic Bank of Egypt, this result is based on a calculated value greater than t table (7.425> 1.671) and the significance value is smaller than the alpha value (0.000 <0.05). the amount of influence exerted by the Islamic business ethics variable on the interest of Indonesian citizens in Egypt to save at Faisal Islamic Banking of Egypt is 46.2 percent. In comparison, the remaining 53.8 percent is influenced by other variables not examined in this study.